2017
DOI: 10.1063/1.4974313
|View full text |Cite
|
Sign up to set email alerts
|

Conformational adaptation and manipulation of manganese tetra(4-pyridyl)porphyrin molecules on Cu(111)

Abstract: Porphyrins are highly flexible molecules and well known to adapt to their local environment via conformational changes. We studied the self-assembly of manganese meso-tetra(4-pyridyl)porphyrin (Mn-TPyP) molecules on a Cu(111) surface by low temperature scanning tunneling microscopy (STM) and atomic force microscopy (ATM). We observe molecular chains along the 110 direction of the substrate. Within these chains, we identify two molecular conformations, which differ by the orientation of the upward bending of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
1
16
0
2
Order By: Relevance
“…20,21 The alternative rotation of the molecular units can be ascribed to the steric repulsive force between the peripheral H atoms of the four py terminals which are linked at a single Na center. 37,38 To reveal the nature of the Na-py interaction, we have conducted XPS experiments, and examined Na 2p and N 1s spectra. In the top panel of Fig.…”
Section: Determination Of the Assembly Structure And Na-py Coordinationmentioning
confidence: 99%
“…20,21 The alternative rotation of the molecular units can be ascribed to the steric repulsive force between the peripheral H atoms of the four py terminals which are linked at a single Na center. 37,38 To reveal the nature of the Na-py interaction, we have conducted XPS experiments, and examined Na 2p and N 1s spectra. In the top panel of Fig.…”
Section: Determination Of the Assembly Structure And Na-py Coordinationmentioning
confidence: 99%
“…The dihedral angle of the pyridyl rings is found to be 70 • with adlayer structure primarily directed by lateral intermolecular interactions. Another PDFT study of MnTPyP on Cu(111) [73] with GGA-PBE [45] showed that MnTPyP adsorbs in a saddle shape due to the rotation and inclination of the pyridyl groups towards Cu adatoms, which stabilize the metal-organic chains. Metalated and non-metalated meso-substituted phenyl porphyrins are some of the extensively studied porphyrins on surfaces [71].…”
Section: Conformational Studies Of Meso-substituted Porphyrins On Submentioning
confidence: 99%
“…Beim AFM dient die Hçhe der Messspitze z*, an der die negative Frequenzverschiebung füre ine bestimmte laterale Position der Spitze am grçßten ist, als Maß fürd ie Adsorptionshçhe. [33,[70][71][72] Darüber hinaus kçnnen auch Metallatome in metallorganischen Komplexen beobachtet und lokalisiert werden. [49] Chemisorption von Molekülen kann von Physisorption unterschieden werden.…”
Section: Adsorptionsgeometrieunclassified
“…[69] Molekulare Konformationen kçnnen präzise voneinander unterschieden und aufgelçst werden. [33,[70][71][72] Darüber hinaus kçnnen auch Metallatome in metallorganischen Komplexen beobachtet und lokalisiert werden. [73][74][75] Die Adsorptionsgeometrie von Pentacen auf Cu(111) ist in Abbildung 2als Karte der Messspitzenhçhe z*dargestellt, welche aus einer 3D-Kraftkarte extrahiert wurde.…”
Section: Ursprung Des Atomaren Kontrasts Auf Molekülenunclassified